2017
DOI: 10.3389/fonc.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Agonists of Vasopressin V2 Receptor Reduce Expression of Neuroendocrine Markers and Tumor Growth in Human Lung and Prostate Tumor Cells

Abstract: Neuroendocrine tumors (NETs) comprise a heterogeneous group of malignancies that express neuropeptides as synaptophysin, chromogranin A (CgA), and specific neuronal enolase (NSE), among others. Vasopressin (AVP) is a neuropeptide with an endocrine, paracrine, and autocrine effect in normal and pathological tissues. AVP receptors are present in human lung, breast, pancreatic, colorectal, and gastrointestinal tumors. While AVP V1 receptors are associated with stimulation of cellular proliferation, AVP V2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…However, ectopic expression of AVP and its receptors has been reported in breast, pancreatic, colorectal and gastrointestinal cancers, and small cell lung carcinoma [4,5]. While V1R activation has been observed to increase tumor cell growth [6,7], V2R agonists are generally known to have angiostatic, anti-proliferative and/or anti-metastatic effects in breast, lung and colorectal cancers [8][9][10]. However, in contrast to these protective roles of V2R, one study reported that V2R activation increased cell proliferation of ccRCC cell lines of human origin in vitro [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, ectopic expression of AVP and its receptors has been reported in breast, pancreatic, colorectal and gastrointestinal cancers, and small cell lung carcinoma [4,5]. While V1R activation has been observed to increase tumor cell growth [6,7], V2R agonists are generally known to have angiostatic, anti-proliferative and/or anti-metastatic effects in breast, lung and colorectal cancers [8][9][10]. However, in contrast to these protective roles of V2R, one study reported that V2R activation increased cell proliferation of ccRCC cell lines of human origin in vitro [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for caution is that experiments on select tumour cell lines have suggested an inhibitory effect of the hormone. Recently for example, Pifano et al [ 33 ] reported on an anti-proliferative effect mediated by the V2-receptor in a tumour cell xenograft model. Such observations would argue against the use of a V2-receptor antagonist in cancer patients; yet there is no evidence in the literature that treatment with an antagonist promotes growth or spread of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has reported that the vasopressin analog desmopressin, a selective agonist for the vasopressin receptor 2 (AVPR2), significantly reduced tumor cell growth and migration in AR-negative CRPC (3). In vitro exposure to desmopressin also induced a dramatic decrease of the neuroendocrine markers chromogranin and neuron-specific enolase in aggressive CRPC cells (3). In prostate cancer, neuroendocrine transdifferentiation is known to be related with transition toward AR-indifference and metastatic phenotype.…”
mentioning
confidence: 95%